Re-modeling the Romanian Fiscal Policy under the Terms of the Economic Crisis - Aura Gabriela SOCOL; Dorin MĂNTESCU (Theoretical and Applied Economics, 2011)

(untitled)
This paper brings arguments for the necessity to re-think the modality to analize and interpret the Romanian fiscal policy, under the terms of the future adheration to the Euro Zone. Under these terms, this study estimates the structural budget deficit, considering this indicator as one of the most relevant for assessing the performance of the fiscal management, and also the extent to which the Romanian fiscal policy is prepared to act as a sole instrument which can stabilize the national economy after entering the Euro Zone. The work is structured as it follows: (i) estimate for the potential GDP and for the output gap by means of the production function method and by the use of the Hodrick- Prescott filter; (ii) estimate for the cyclic budget component, based on the deficit sensitivity (using the elasticities of the government revenues and purchases related to the GDP) and on the value of the output gap and, subsequently, of the structural budget component. Finally, the work mentions a series of conclusions and recommendations regarding the methodological re-construction of the assessment for the fiscal policy’s efficiency.